Practical application of thermodynamics in the optimal synthesis of chemical and biotechnological processes (2015)
In most chemical engineering design problems it is required a complex set of research steps so as to establish the operating conditions in which the process reaches the highest conversion, yield and productivity. However, these steps are tedious, complex and can lead to mistakes. To differ from this, the coupled application of the thermodynamics and the graph-theory appears can be considered as an alternative to design chemical and biotechnological processes. So, in that way, this master’s thesis presents a strategy to synthetize, to design and to evaluate conventional and non-conventional process schemes using Process Engineering techniques from a complete set of different configurations that corresponds to maximal yield of a target product to find good initial estimates to perform calculations and rigorous simulations. A theoretical evaluation was followed to corroborate different possibilities in operation conditions provided for the models for both types of approaches. This kind of evaluation was therefore particularly useful for assessing feasibility of chemical production systems and moreover it provided a realistic measure of the potential for improving the efficiency of the overall process (Texto tomado de la fuente)